Juridical Analysis of Constitutional Court Rulings Regarding Testing Legal Form - Hafizar, Achmad; Syahuri, Taufiqurrohman; Triadi, Irwan (LifeSciFi, 2025)
The legal consequence of this decision was that the Constitutional Court granted the lawmakers a two-year period to amend the Job Creation Law, following a process that adheres to a clear, standardized, and established method for creating omnibus laws. The Constitutional Court's Decision No. 91/PUU-XVIII/2020 was subsequently followed by the government issuing Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation, which contains similar content to the Job Creation Law. This has sparked controversy within the public. Therefore, the issue that will be further examined in this research is how the creation of the Job Creation Government Regulation In lieu of Law complies with the Constitutional Court's Decision No. 91/PUU-XVIII/2020, which declared the law conditionally unconstitutional, and how the harmonization between the Job Creation Government Regulation In lieu of Law and the legal reasoning in the Constitutional Court's decision is achieved. The research method used in this study is a normative juridical approach, which emphasizes library research. This study is descriptive-analytical, with the research stages focusing on secondary data analysis. Data collection techniques include library research and field research through interviews with relevant parties. The results of the study show that the lawmakers did not comply with the Constitutional Court's Decision No. 91/PUU-XVIII/2020, as they did not amend the Job Creation Law as required by the decision. Instead, they chose to issue the Job Creation Government Regulation In lieu of Law. Regarding the harmonization between the Job Creation Government Regulation In lieu of Law and the legal reasoning in the Constitutional Court's Decision No. 91/PUU-XVIII/2020, a lack of harmonization between the two was found.